The Laughing Classroom: Humor, Teaching, and Learning - Anne Lou M. Hendriks (Fakultas Filsafat Universitas Advent Indonesia, 2021)
Diverse strategies are employed nowadays to ascertain effective teaching- learning process. Among these methods chosen to achieve desired result is the making use of humor—a teaching approach which has been discerned as an effective way of creating a more productive teaching and learning, may it be language. This paper discusses the place and importance of humor to teachers, learners, and education as a whole. Barriers and guidelines to using humor are also discussed. The Biblical foundation of humor stresses the benefits humor (laughter) gives.